Level Of Satisfaction Of The Family Responsible For Hospitalized Neonatos About The Nursing Care Provided In The Neonatal Intensive Care Unit At The Maternal Perinatal National Institute - 2016 - Gómez-Sangama, Ivelisse (2017)
Objective. To describe the level of satisfaction of the responsible for hospitalized newborns, on accessibility, explanation, facilitation, comfort, anticipation, maintaining a relationship of trust, monitoring and tracking nursing care provided in the Neonatal Intensive Care Unit (NICU). Materials and methods. Descriptive and cross section study of 30 family responsible for hospitalized newborns in the NICU in January 2016. The technique used was the survey.